SEISMIC BEHAVIOR OF ADOBE MASONRY WALLS IN 2006 EARTHQUAKE SILAKHOOR, IRAN - Zamankhani, Jalal Salek; Arun, Gorun (YILDIZ TECHNICAL UNIV, 2011)
Adobe has traditionally been the primary construction material in Iran. Performance of traditional adobe construction during numerous earthquakes in Iran has generally been poor. In this research the influence of physical properties of adobe masonry walls on their seismic behavior has been studied. First, some of the undamaged and damaged buildings in Silakhor earthquake were selected and by using the information forms designed for this purpose, entire physical properties of 43 adobe walls and their accurate damage specifications were collected. The analyses done by SPSS software on the collected data, relation between wall properties and vulnerability severity level have been studied.
Keywords: Masonry structures; seismic performance; earthquake damages; adobe wall; Engineering